2015
DOI: 10.1017/s1751731115001524
|View full text |Cite
|
Sign up to set email alerts
|

Impact of barley form on equine total tract fibre digestibility and colonic microbiota

Abstract: This study aimed at assessing the impact of four barley forms on total tract apparent digestibility of dietary fibre in horses fed a large amount of starch in the morning meal (0.27% BW). Processed barley forms had a greater pre-caecal starch digestibility than the whole form. Based on this result, we hypothesised that using barley-processing methods would limit the potential dumping of undegraded starch in the hindgut of horses and, consequently, the potential negative effect on fibre degradation in the hindg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 26 publications
1
11
1
1
Order By: Relevance
“…Furthermore, both the botanical source and feed processing of starch have been shown to impact upon starch digestion [12,13]. Feeding thermo-mechanical forms of barley as opposed to whole grain or mechanically-treated forms of barley has been shown to result in greater ADF (acid detergent fibre) digestibility, and suggests that feeding thermomechanical forms of barley may limit the amount of undigested starch reaching the hindgut [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, both the botanical source and feed processing of starch have been shown to impact upon starch digestion [12,13]. Feeding thermo-mechanical forms of barley as opposed to whole grain or mechanically-treated forms of barley has been shown to result in greater ADF (acid detergent fibre) digestibility, and suggests that feeding thermomechanical forms of barley may limit the amount of undigested starch reaching the hindgut [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…Concentrate feeding was therefore reported to cause changes in the hindgut microbial ecosystem in horses (Grimm, Philippeau, & Julliand, ; Julliand, De Fombelle, Drogoul, & Jacotot, ; Moore & Dehority, ). In particular, the cellulolytic bacteria (Julliand et al., ) and the total population of functional bacteria in the colonic contents of horses (Philippeau, Sadet‐Bourgeteau, Varloud, & Julliand, ) are compromised by concentrates like barley. In the literature, it has been shown that feeding concentrate after or along with the forage portion of the diet could, to some extent, help maintaining an appropriate hindgut physiochemical environment (Jensen, Austbø, & Tauson, ; Sadet‐Bourgeteau et al., ; Zeyner, Geiβler, & Dittrich, ).…”
Section: Introductionmentioning
confidence: 99%
“…Philippeau et al. () demonstrated that using thermo‐mechanically treated cereals limits the potential negative impact of starch on fibrolytic activity in horses. To our knowledge, the combination of a strategic feeding sequence (FS) and a hydrothermal processing of cereals with the purpose of improving hindgut fermentation in concentrate‐fed horses has not yet been tested.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Em animais de produção, alterações na composição da dieta podem levar a mudanças significativas na ecologia microbiana gastrointestinal, concorrendo para a queda de produtividade destes animais (CALLAWAY et al, 2010). Dentre os animais, podemos destacar os equinos, os quais são alvos de pesquisas sobre a microbiota intestinal (MUHONEN et al, 2009;SHEPHERD et al, 2012;COSTA et al, 2015b;PHILIPPEAU et al, 2015;COVERDALE, 2016). Existe uma abundância de microrganismos que colonizam todo o TGI dos equinos como fungos, bactérias, protozoários e arqueas (CUMMINGS e MACFARLANE, 1997;FRAPE, 2008); com isso, pesquisas têm sido realizadas para fornecer informações sobre populações alvo específicas (DE-FOMBELLE et al, 2003;AL JASSIM et al, 2005;HARLOW et al, 2015 (MOREAU et al, 2014;AL JASSIM et al, 2005;DE-FOMBELLE et al, 2003).…”
Section: Microbiologia Do Trato Gastrointestinal Equinounclassified